HEMATOPOIETIC CELL TRANSPLANTATION (HCT) FOR ALL: A report from the 2024 Congress of the Brazilian Bone Marrow Transplantation and Cellular Therapy Society (SBTMO) - Barroso Duarte, Fernando; Sampaio Nunes Barroso, Karine; Guilherme Darrigo Juniro, Luiz; Maria Sales Bonfim, Carmem (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2024)
This article analyzes current data, and the main challenges faced in Hematopoietic cell Transplantation (HCT) in Brazil, as presented at the SBTMO 2024 meeting, with the aim of guiding future actions. Topics discussed included the waiting list for HCT transplants, access to beds for adults and pediatric patients, and the need for a more efficient distribution of resources across the country. Among the identified needs were the creation of a program to expand access to transplants through the Brazilian Unified Health System (SUS), the importance of health registries for data-driven decisions, and the development of the "Mais Saúde Amazônia" project to expand transplant centers in the Amazon region. Additionally, the provision of financial incentives for transplant centers, the implementation of mentorship programs to increase access to HCT, and the formation of a cooperative network between SBTMO (Brazilian Society of Bone Marrow Transplantation and Cellular Therapy), ABHH (Brazilian Association of Hematology, Hemotherapy, and Cellular Therapy), ANVISA (Brazilian Health Regulatory Agency), ABRALE (Brazilian Association of Lymphoma and Leukemia), and INCA (Brazilian National Cancer Institute) to improve the integration of HCT services were discussed